Respuestas
Respuesta dada por:
4
de manera practica es despejar x en función a f(x)
por ejemplo
![f(x) = \frac{-2x-1}{5} \\ \\ 5f(x)=-2x-1 \\ \\ 2x+1=-5f(x) \\ \\ 2x=-5f(x)-1 \\ \\ x= \frac{-5f(x)-1}{2} f(x) = \frac{-2x-1}{5} \\ \\ 5f(x)=-2x-1 \\ \\ 2x+1=-5f(x) \\ \\ 2x=-5f(x)-1 \\ \\ x= \frac{-5f(x)-1}{2}](https://tex.z-dn.net/?f=f%28x%29+%3D+%5Cfrac%7B-2x-1%7D%7B5%7D++%5C%5C++%5C%5C++5f%28x%29%3D-2x-1++%5C%5C++%5C%5C+2x%2B1%3D-5f%28x%29+%5C%5C++%5C%5C+2x%3D-5f%28x%29-1+%5C%5C++%5C%5C+x%3D+%5Cfrac%7B-5f%28x%29-1%7D%7B2%7D+++)
remplazando f(x) = x
![x= \frac{-5f(x)-1}{2} \\ \\ f(x)= \frac{-5x-1}{2} \\ \\ funcion \\ inversa
x= \frac{-5f(x)-1}{2} \\ \\ f(x)= \frac{-5x-1}{2} \\ \\ funcion \\ inversa](https://tex.z-dn.net/?f=x%3D++%5Cfrac%7B-5f%28x%29-1%7D%7B2%7D++%5C%5C++%5C%5C+f%28x%29%3D++%5Cfrac%7B-5x-1%7D%7B2%7D++%5C%5C++%5C%5C+funcion++%5C%5C+inversa%0A%0A)
saludos ISABELA
por ejemplo
remplazando f(x) = x
saludos ISABELA
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años